Non‐linear Photoexcited Negative Differential Conductivity in Bulk SrTiO3 Single Crystals - Alexander Connor Newing; Marin Alexe (Advanced Electronic Materials)
Abstract Current density curves for the [100], [110], and [111] crystallographic directions of photoexcited, nominally pure, bulk SrTiO3 are studied, revealing a strong anisotropy between these crystallographic directions. In the [110] direction two distinct peaks in the current‐voltage characteristics with two different negative differential conductivity regions are distinguishable. The two regions can be explained with two different mechanisms, one based on field‐enhanced trapping and the second the transferred electron effect based on two‐valley conduction band interacting with a trap. Photoluminescence spectra revealed Cr impurities to be the potential origin of the current density anisotropy. In the high temperatures range and low photon fluxes the photoconductivity follows a classical Hecht model with a mu‐tau (μτ) value up to 10−4 cm2 V−1.